The volume of press display advertising in Ireland, 1957 - Kingston, W. V.; Prendiville, B. J. (Statistical and Social Inquiry Society of Ireland, 1958)
Advertising is frequently examined by sociologists and economists from the aspect of its effect on patterns of living and the economy generally. But its dimensions in modern economies suggest that it warrants study in its own right, simply as an economic activity. In 1957, total advertising expenditure in the United States amounted to $10.5 billion, just on 2.5% of the National Income. In the same year, spending in the United Kingdom was between #340 - 365 million, just on 2% of the National Income. The calculations included in the following paper are offered as a necessary first step towards arriving at similar estimates for the Republic of Ireland, both in the absolute, and in terms of the proportion of national resources which are being devoted to Advertising.
Keywords: Advertising expenditure; Press display advertising; Advertising in Ireland; 314.15